Mis-Tagging Phenomena and Impoliteness Expression of Indonesian Netizens: A Study of Cyberpragmatics - Umaroh, Liya (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The Mis-tagging recently is common issue surround Indonesian netizens. Exploding trending topic on social media platform easily often rush to share. This study proposes to describe the mis-tagging phenomena and Impoliteness expression of Indonesia netizens particularly on Instagram. Descriptive qualitative implements as a research method together with cyberpragmatic approach. Source of data were selected comments on Instagrams which describe impoliteness expression. Culpeper’s impoliteness strategies are used for analyzing the research finding. Thus, result of this study describes three strategies on expressing impoliteness; bald on record impoliteness, negative politeness, and sarcasm or mock politeness. Mis-tagging persistently indicate by Indonesian netizens because of uncontrol speed information sharing thus, verifying information before sharing is a key to reduce the mis-tagging phenomena.